Effect of essential oils on seed borne Fusarium sp., and seed quality of sesame (Sesamum indicum L.) - K GIRISH; Chaithra T S; Syeda Kousar Fathima (Journal of Tropical Life Science, 2021)
Sesame is as an important oilseed crop and seed borne fungi are reducing the yield as well as quality of the seeds produced. The present study aimed to evaluate the effect of essential oils for control of seed borne fungi as well as enhancement of seed quality of sesame. Fusarium sp., was isolated from sesame seeds by agar plate method. Four essential oils such as camphor oil, cinnamon oil, clove oil and rose oil were screened for their antifungal potential against the isolated Fusarium sp., by poisoned food method. Selected essential oils were tested at different concentrations of 100, 200, 300, 400 and 500 ppm concentrations for their ability to inhibit the mycelial growth of test fungi. All the oils completely inhibited the mycelial growth of test fungi at 500 ppm concentration. The effect of selected essential oils on sesame seed quality was analyzed by standard blotter method. All the four oils increased the germination percentage and seed vigour while the fungal infection was completely inhibited without any phytotoxic effects. These results observed of the essential oils indicate the possible usage of them for the sesame seed treatment following further investigations.